Chemotherapeutic properties and side-effects associated with the clinical practice of terpene alkaloids: paclitaxel, docetaxel, and cabazitaxel - Sousa-Pimenta, Mário (2023)
Over the years, many biological and synthetic agents have been explored and tested in attempts to halt the spread of cancer and/or cure it. Currently, several natural compounds have and are being considered in this regard. For example, paclitaxel is a potent anticancer drug that originates from the tree Taxus brevifolia. Paclitaxel has several derivatives, namely, docetaxel and cabazitaxel. These agents work by disrupting microtubule assembling dynamics and inducing cell cycle arrest at the G2/M phase of the cell cycle, ultimately triggering apoptosis. Such features have helped to establish paclitaxel as an authoritative therapeutic compound against neoplastic disorders. After the completion of compound (hemi) synthesis, this drug received approval for the treatment of solid tumors either alone or in combination with other agents. In this review, we explore the mechanisms of action of paclitaxel and its derivatives, the different formulations available, as well as the molecular pathways of cancer resistance, potential risks, and other therapeutic applications. In addition, the role of paclitaxel in hematological malignancies is explored, and potential limitations in the therapeutic use of paclitaxel at the clinical level are examined. Furthermore, paclitaxel is known to cause increased antigen presentation. The immunomodulatory potential of taxanes, alone or in combination with other pharmacologic agents, is explored. Despite terpene-alkaloids derivatives' anti-mitotic potential, the impact of this class of drugs on other oncogenic pathways, such as epithelial-to-mesenchymal transition and the epigenetic modulation of the transcription profile of cancer cells, is also analyzed, shedding light on potential future chemotherapeutic approaches to cancer.